Impact of green transition on sustainable development in Saudi Universities- Applied Study College of Business Administration - Northern Borders University - Ibrahim, Ahmed Ibrahim Hassan (Zielona Góra: Faculty of Economics and Management Press)
Introduction Purpose - This article aims to study the impact of green transformation practices in Saudi universities on sustainable development. Some practices derived from previous studies as well as the Millennium Sustainable Development Goals were highlighted. The importance of studying these practices that related to sustainable development in universities is due to three reasons, the first of which is preserving the environment surrounding the university and its impact on sustainability, and the second is that the university offers in its curricula many courses on sustainable development and research programs.
Keywords: green transition practices in universities; sustainable development; sustainability